新型重载摩擦离合器 - 梁以德; 梁慧芳 (Jixie chuandong)
A modern version friction clutch is introduced. Friction coefficient of the clutch is 10-30 times larger than that of the common friction clutch. There are a lot of advantage of the clutch, such as the volume is small, power transmitted is great, the structure is simple, technological behaviour is good, cost is lows, life is long. Therefore, It is an ideal friction clutch of modern version.